CLASSIFICATION IN A SERVICE INDUSTRY BASED ON ENTREPRENEURIAL ORIENTATION - Ahmed Salem Hassan Alfaifi, Ali Saeed A Alqahtani, Ismail Jubran Hussain Nammazi , Yasser Abdullah Algarni, Sultan Musaad Obaidan Alharbi, Ahmed Abdullah Hassan Alqarni, ,; Ali Saleh Hassan Alghamdi, Ahmad Noman Alsaleh, Faisal Khalid Naji Alshammari, Alanazi Sulaiman Qaem, Ibrahim Suliman Alaboudi, Ahmed Abdullah Kaabi, Abdulelah Neda Alshammari, Abdullatif Mohammed Alessa, ,; Abdulelah Nuhayter Alshammari, Abdulrahman Abdullah Ali Alassaf, Muneerah Suliman Aldoukhi, Bander Abdullah Alotaibi, Lamia Abdullah Almahaiza, (Chelonian Research Foundation, 2022)
Research on service classification has thus far mostly adopted a macro perspective, utilizing factors like client interaction or labor intensity to create service typologies or taxonomies. These classification schemes tend to approach a whole industry, like airlines, as a single homogenous entity, even if they are useful in understanding crucial management concerns and positioning strategies between service industries. Nonetheless, businesses within the same sector frequently employ intangible assets, including entrepreneurial orientation programs, to outbid one another. According to the resource-advantage theory, companies can achieve superior performance by developing long-term strategies and a sustainable competitive advantage through the use of intangible resources. In order to categorize organizations within the retailing business, we created organization clusters based on entrepreneurial orientation as intangible resources. We investigated whether the entrepreneurial inclinations of the resulting groups within the pharmacy industry were associated with their perceptions of the environment, organizational characteristics, and performance outcomes using data from the retail pharmacy sector. One of the study's contributions is the operationalization of the concept of entrepreneurial orientation. Key Words: Classification Scheme, Taxonomy, Entrepreneurial Orientation, Intangible Resources.